Sistem Pendukung Keputusan Penentuan Dakian Gunung Di Pulau Jawa Menggunakan Fuzzy Logic Mamdani - Nurmala, Nurmala; Hastono, Tri; Janah, Siti Nuraitul (Jurusan Sistem Informasi Universitas Islam Negeri Alauddin Makassar, 2024)
Mountain climbing is an activity with a relatively high level of danger that requires climbers to walk in the forest and spend quite a long time with increasingly low oxygen levels and very cold temperatures that can even reach 0 degrees Celsius. In this research, decisions play an important role in determining mountain climbing routes. especially on the island of Java which has a variety of mountains with different characteristics, therefore we help climbers in choosing mountain climbs that suit their individual preferences and personal conditions. The method used is Mamdani's Fuzzy Logic which can overcome uncertainty and complexity of information in decision making. To collect data regarding height, distance, track length and climbing costs, namely through interviews and related analysis. Fuzzy Logic Mamdani is implemented to manage and process related data and can produce output in the form of recommendations for climbing routes. This fuzzy model can integrate environmental variables, such as height, distance, cost and track length.